Antarctic and subantarctic Corallinaceae - Foslie, M. (Mikal), 1855-1909; Svenska sydpolar-expeditionen (1901-1903) (Stockholm : Lithographisches Institut des Generalstabs, 1907)
Mode of access: Internet.